2017
DOI: 10.1071/rd15481
|View full text |Cite
|
Sign up to set email alerts
|

Proteome of equine oviducal fluid: effects of ovulation and pregnancy

Abstract: The equine oviduct plays a pivotal role in providing the optimal microenvironment for early embryonic development, but little is known about the protein composition of the oviducal fluid in the horse. The aim of the present study was to provide a large-scale identification of proteins in equine oviducal fluid and to determine the effects of ovulation and pregnancy. Four days after ovulation, the oviducts ipsilateral and contralateral to the ovulation side were collected from five pregnant and five non-pregnant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 75 publications
6
33
0
Order By: Relevance
“…Quantitative proteomics have further verified the hormonal regulation of bovine and ovine ODF proteins and have demonstrated gamete induced changes in the ODF proteome of pigs . Furthermore, the effect of the presence of an embryo on the ODF protein profile has been demonstrated in mares …”
Section: Introductionmentioning
confidence: 84%
“…Quantitative proteomics have further verified the hormonal regulation of bovine and ovine ODF proteins and have demonstrated gamete induced changes in the ODF proteome of pigs . Furthermore, the effect of the presence of an embryo on the ODF protein profile has been demonstrated in mares …”
Section: Introductionmentioning
confidence: 84%
“…Recently, our knowledge on the proteomic content of OF in mammals has greatly increased thanks to mass spectrometry. Proteomes of the tubal fluid have been obtained in pigs [35,36], dogs [37], sheep [38], cattle [39][40][41], horse [42], rabbit [43], and human [44]. The most abundant proteins in oviductal secretions include serum albumin, oviductin (OVGP1), heat shock proteins (HSP90B1, HSP90AB1, HSP90AA1, HSPA8, HSPA1B, HSPA5), annexins (ANXA1, ANXA4), tubulin subunits (TUBB5, TUBA4A), complement C3 (C3), and myosins (MYH9, MYH14) [38][39][40].…”
Section: Proteinsmentioning
confidence: 99%
“…It has been demonstrated that the oviductal proteome changes with the different stages of the oestrous cycle (Lamy et al 2016; Soleilhavoup et al 2016), the presence of gametes (Georgiou et al 2005) or the presence of embryos (Smits et al 2017). The proteome of the oviduct epithelial cells has also been studied in humans (Wang et al 2016) and pigs (Seytanoglu et al 2008).…”
Section: Introductionmentioning
confidence: 99%